2008
DOI: 10.1007/s11237-008-9004-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-chemical evidence for the possible existence of a new isomer of dinitrogen tetraoxide

Abstract: The geometric, electronic, and thermodynamic parameters of six known isomers of the molecular structure of dinitrogen tetraoxide N 2 O 4 were calculated by the quantum-chemical DFT/B3LYP density functional method with the 6-311++G(3df) basis set. The structure of a new isomer of dinitrogen tetraoxide NONO 3 , which is characterized by a local potential energy minimum and corresponds to a stationary state of the N 2 O 4 isomer, was calculated. The DFT calculations showed that this structure NONO 3 is characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The geometric, electronic, and energy parameters of other isomers of the N 2 O 4 molecular structure were also calculated [3,4,16], and the most stable structure of cis-cis О=NO-ОN=O peroxide was proposed as the intermediate of the oxidation reaction [3,4] 2NO…”
Section: Reaction Models and Calculation Proceduresmentioning
confidence: 99%
“…The geometric, electronic, and energy parameters of other isomers of the N 2 O 4 molecular structure were also calculated [3,4,16], and the most stable structure of cis-cis О=NO-ОN=O peroxide was proposed as the intermediate of the oxidation reaction [3,4] 2NO…”
Section: Reaction Models and Calculation Proceduresmentioning
confidence: 99%
“…Vibrational spectrum of nitroso nitrate: Large discrepancies in the experimental vibrational frequencies have been reported for ONONO 2 produced under different experimental conditions, [59] which may be attributed to 1) a high degree of conformational flexibility; [64] 2) its large dipole moment (m % 2.6 D), [61] suggesting strong interactions with polar environments; and 3) the assumed co-existence of three isomeric species: trans-and cis-ONONO 2 with respect to the nitrosooxy ONÀO single bond and ionic nitrosonium nitrate, NO + NO 3 À . [15,24,[43][44][45] Indeed, in former matrix-isolation studies both cis-and trans-ONONO 2 (denoted as D' and D, respectively) were tentatively assigned.…”
Section: Resultsmentioning
confidence: 99%
“…[39][40][41] Although such (NO 2 ) 2 dimers may rapidly dissociate in the gas phase to form 2 NO 2 free radicals, they might be trapped as a radical pair in low-temperature rare-gas matrices, because significant activation barriers have been predicted theoretically for their rearrangement into ONONO 2 and sym-N 2 O 4 . [40,41] Weakly bound (NO 2 ) 2 radical pairs probably play a crucial role also in the sym-N 2 O 4 -trans-ONONO 2 isomerisation, for which computational attempts to find a lowenergy pathway failed, [41,[59][60][61] or in the rapid gas-phase isotopic exchange reactions of isotopically labelled NO 2 [Eq. (5)]: [62] …”
Section: à1 ð1þmentioning
confidence: 99%
See 1 more Smart Citation
“…In connection with these data and also the results from [13], in which it was shown that NO 3 is formed during one-photon irradiation (l = 436.45 nm, P = 10 -13 -10 1 torr) of gaseous NO 2 , we undertook a detailed quantum-chemical investigation of the conversion of NO 2 into NO 3 . Earlier we had already noticed [14] that in the NO 2 + NO 2 system under various physical influences (low temperatures, UV irradiation) not only dimerization processes NO 2 + NO 2 ® N 2 O 4 but also transformations of the dimers into molecular structures of the nitrosonium nitrate type NONO 3 are possible. The results of the kinetic experiments carried out in [13] show that NO 3 can be formed through reaction of the electronically excited state of nitrogen dioxide NO 2 * with the molecules of the ground state: NO 2 * + NO 2 « NO + NO 3 .…”
Section: The Reactivity Of Nitrogen Dioxide In the High-energy State mentioning
confidence: 99%